Respuesta :

For this case we have a function of the form:

[tex]y = f (x)[/tex]

Where:

[tex]f (x) = - 4x ^ 2-3x + 2[/tex]

We must find the value of the function when[tex]x = -2[/tex], that is, [tex]g (-2)[/tex]. So:

[tex]g (-2) = - 4 (-2) ^ 2-3 (-2) +2[/tex]

We have to:

[tex]- * - = +\\- * + = -[/tex]

So:

[tex]g (-2) = - 4 (4) + 6 + 2\\g (-2) = - 16 + 8[/tex]

Different signs are subtracted and the major sign is placed.

[tex]g (-2) = - 8[/tex]

Answer:

[tex]g (-2) = - 8[/tex]

ACCESS MORE